Diversity of Non-Volant Small Mammals in Pulau Tinggi, Johor, Malaysia - SITI AISHAH, JAMALUDDIN; Mohd Ridwan, Abdul Rahman; NURSYUHADA, OTHMAN; Hidayah, Haris; FATIN NUR ATIKAH, ZAHARI; MOHD FAUDZIR, NAJMUDDIN; MD ZAIRI, ZAINAL; Muhammad Abu Bakar, Abdul Latiff (Penerbit UMT, 2022)
A non-volant small mammal survey was conducted at Pulau Tinggi between July and September 2019. This study aimed to provide baseline data for non-volant small mammals in Pulau Tinggi by setting 55 cage traps and 20 pitfalls for 44 trapping nights. A total of 20 individuals of non-volant small mammals were documented, representing five species from three families: Soricidae, Sciuridae and Muridae. The Rajah spiny rat (Maxomys rajah) and the Red spiny rat (Maxomys surifer) were the most abundant species (n=6) of non-volant small mammals in Pulau Tinggi. The Malayan field rat (Rattus tiomanicus) was the least species (n=1). The Malayan shrew (Crocidura malayana) is the only shrew recorded on the island. The analysis of similarities between our study site and other Malaysian islands reveals that Pulau Tinggi shares more similarities with Pulau Pangkor and Pulau Perhentian than Pulau Tioman. The small mammal richness on Pulau Tinggi is relatively low compared to other islands, most likely due to the study site’s limited coverage and time constraints. Long-term monitoring is required to determine the true diversity of species and distribution of small mammals on Pulau Tinggi.